Analysis Methodology For Establishing Tartrazine Levels In Food And Beverage Products: A Review - Gusti Ayu Dian Nanda Pratiwi As; I Made Arie Dharma Putra Nugraha; Mohammad Fajar Hadi Salim; I Putu Aditya Maha Putra (Mutiara: Multidiciplinary Scientifict Journal, 2023)
Food and beverage manufacturers in today’s industry tend to use dyes to give a distinctive color characteristic to a product. Manufacturers tend to use synthetic dyes, like tartrazine, rather than most natural dyes. It should be noted that in some cases, manufacturers did not care about the testing of the levels of chemical dyes used before the product is marketed, thus manufacturers were not responsible for the potential dangers, particularly the risk of toxicity, and also out of range dye levels from the permissible Acceptable Daily Intake (ADI) values. This review aims to update the knowledge of producers or the health department regarding the appropriate analytical methodology, both sample preparation and analytical methods to obtain an accurate image of the levels of tartrazine dye in food and beverage products. The recommended sample preparation method in tartrazine analysis is the Dispersive Solid Phase Extraction (d-SPE) method known as the QuEChERS method (quick, easy, cheap, efficient, rugged, and safe). The analytical method that has high specificity and sensitivity to be used in tartrazine analysis is the High-Performance Liquid Chromatography (HPLC) method, while the UV-Vis Spectrophotometry analysis method offers a fast and low-cost analysis method compared to other methods.